Risk and Insurance - Denenberg, Herbert S.; Eilers, Robert D.; Melone, Joseph, J. (Englewood Cliffs, N.J.: Prentice-Hall, 1974)
The book is largely consumer-oriented. In keeping with the trend toward giving the student a broader perspective, the authors analyze the nature and impact of significant risks in business and personal life and present the available methods for treating them.
Includes bibliographical references.
ne 15/05/2018
Loans
Keywords: Risk (Insurance); Insurance